Reaksi Pasar Modal Terhadap Pengumuman Pertama Kasus Positif COVID-19 Di Indonesia - Lasmana, Andy; Susandra , Farizka; Warizal , Warizal; Arrahman , Arif (Jurnal Akunida, 2022)
This study aims to examine the reaction of the capital market to the announcement of the first positive cases of Covid-19 in Indonesia in manufacturing companies, especially the Multi-Industry sector listed on the Indonesia Stock Exchange. This study uses the Event Study method by taking the events of the first announcement of a positive case of Covid-19 in Indonesia which was published on March 2, 2020 by the president of Indonesia, Joko Widodo. This research was conducted to determine the information content and to see the reaction of the event by looking at the difference between Average Abnormal Return and Average Trading Volume Activity. Data taken 7 days before and 7 days after the announcement of the first positive case of Covid-19 in Indonesia. The results showed that: (1) There was no significant difference in the average Abnormal Return between before and after the announcement of the first positive case of Covid-19 in Indonesia. (2) There is a significant difference in average Trading Volume Activity between before and after the announcement of the first positive case of Covid-19 in Indonesia.